STUDI LITERATUR PENGEMBANGAN PARIWISATA BAHARI BERBASIS MASYARAKAT COMMUNITY BASED MARITIME TOURISM DEVELOPMENT LITERATURE STUDY - Anis Munandar; Rudi Febriamansyah; Erwin Erwin; Melinda Noer (Menara Ilmu, 2020)
As an archipelago, Indonesia has a lot of marine tourism potential. Its development can help the economic growth of the State and society. To develop maritime tourism can be done with a variety of approaches, one of them through a bottom-up approach that is community based. So that the proposition can be proven theoretically correct, it is necessary to study literature about the development of community-based marine tourism and this is at the same time the goal of research. This research belongs to the type of library research. The data used are secondary data from various sources, especially scientific journals obtained from scientific journal websites (national and international), Open Journal of Access, and Google Scholar. Data collection techniques used are documentation techniques. The focus of the data in this study is the study of literature on the general description of Indonesian marine tourism and theoretical conceptual literacy as well as previous research on community-based marine tourism development and theories or concepts related to community-based development / development. The data analysis technique used is descriptive qualitative through analysis tools, namely content analysis. Many marine tourism potentials and destinations are scattered throughout the administrative regions of Indonesia. Indonesian marine tourism resources that are worldwide, such as biodiversity of coral reefs, snorkeling spots, dive spots, and surfing spots. To develop maritime tourism can be done by optimizing the potential of the community, such as local wisdom, culture, customs, religion. This approach is better known as community-based development / development. In its implementation, it needs accurate strategy and good planning so that the goal of developing marine tourism can be achieved well. Keywords: economic growth, coastline, islands, marine tourism